ICT-Enabled Grievance Redressal in Central India: A Comparative Analysis - Marathe, Meghana; O'Neill, Jacki; Pain, Paromita; Thies, Bill (ACM - Association for Computing Machinery, 2016)
Helping citizens to resolve grievances is an important part of many e-governance initiatives. In this paper, we examine two contemporary initiatives that use ICTs to help citizens resolve grievances in central India. One system is a state-run call center (the CM Helpline), while the other is an independent citizen journalism service (CGNet Swara). Despite similarities in their high-level goals, approach, and geographies served, the systems have key differences in their use of technology, their level of transparency, and their relationship to government. Using qualitative interviews, field immersions, and other data, we analyze how these differences impact the experiences of citizens, officials, and the intermediaries between them. We synthesize our observations into a set of recommendations for the design of future ICT-enabled grievance redressal systems.